2006
DOI: 10.1111/j.1745-7262.2006.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous primary carcinomas of the bladder and prostate

Abstract: Although the incidence of incidental prostate cancer in patients in Taiwan with bladder cancer is not high compared with that in Western countries, we suggest that digital rectal examination and prostate-specific antigen (PSA) are important screening tools for men with bladder cancer, especially for those aged 60 years and older in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 10 publications
4
31
2
2
Order By: Relevance
“…In this study, we found that the frequency of incidental PCa in China was 3.3%, similar to the frequency in Lee et al [10] and Yumura et al [7] studies (4% and 5.1%, respec tively), but was much lower than the frequency in other series of RCP cases (14% to 60%) [19] and the ageadjusted frequency of autopsy-detected PCa in China [4].…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…In this study, we found that the frequency of incidental PCa in China was 3.3%, similar to the frequency in Lee et al [10] and Yumura et al [7] studies (4% and 5.1%, respec tively), but was much lower than the frequency in other series of RCP cases (14% to 60%) [19] and the ageadjusted frequency of autopsy-detected PCa in China [4].…”
Section: Discussionsupporting
confidence: 45%
“…Of these npg patients, three had carcinoma in situ (CIS) involving the pro s tatic urethra and six had TCC involving the prostate glands/parenchyma. Our literature review identified eight articles from Korea, Japan, Iran, India, Taiwan, China and mainland China that we believe could represent the whole Asian population [7][8][9][10][11][12][13][14]. We combined our data with the data from the reviewed literature for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidental prostate carcinoma rates detected in cases having undergone RCP due to bladder tumor vary between 4% and 60% (Table 2) (2,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). One of the reasons for these various rates has been linked to the use of section intervals in different widths.…”
Section: Discussionmentioning
confidence: 99%